Tax Subsidy for Long-term Care Insurance - Thomas Neusius (Wirtschaftsdienst)
Abstract Germany’s long-term insurance is subject to financial pressure: Various reforms throughout the last few years have considerably extended the benefits. Consequences affect both the public and private providers of the long-term insurance whose policies offer identical entitlements. In the public branch, financing was partially insufficient and the pay-as-you-go scheme is hit by demographic ageing; the private branch, relying on live insurance like premium calculation, saw severe premium adjustments amplified by the low level of interest rates. To protect employees who are covered in most cases by public insurance, tax subsidies from a contribution hike are to be introduced in favour of the public insurance scheme. This poses several questions concerning the justification of the transfer and the coexistence of public and private insurance.